Hubungan Tingkat Pengetahuan Pasien Hiperkolesterolemia Dengan Ketepatan Penggunaan Obat Simvastatin Di Apotek Kecamatan Weru Sukoharjo - Kania Istiqomah; Hanugrah Ardya Crisdian Saraswati; Sardjiman Sardjiman (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2024)
Hypercholesterolemia is an elevation of cholesterol levels exceeding 240 mg/dl. Simvastatin is a cholesterol-lowering drug classified as a statin. Improper medication use is often due to incomplete or incorrect information obtained by patients, which can impact their level of knowledge. The purpose of this research is to determine the relationship between patients' knowledge levels on hypercholesterolemia and the accuracy of simvastatin medication use at pharmacies in Weru Sub-District, Sukoharjo. The study was an analytical observational study with a cross-sectional research design. Sample selection used purposive sampling based on inclusion and exclusion criteria. The instrument for this research utilized a questionnaire distributed to 110 respondents. The research findings revealed a correlation coefficient value of 0.383 and a significant value (P Value) of 0.001<0.05, indicating that the alternative hypothesis was accepted. In conclusion, there was a significant correlation between the variables of patients' knowledge levels on hypercholesterolemia and the accuracy of simvastatin medication use at pharmacies in Weru Sub-District, Sukoharjo.